2017
DOI: 10.1038/s41598-017-03010-6
|View full text |Cite
|
Sign up to set email alerts
|

Development of a 3D angiogenesis model to study tumour – endothelial cell interactions and the effects of anti-angiogenic drugs

Abstract: The tumour microenvironment and tumour angiogenesis play a critical role in the development and therapy of many cancers, but in vitro models reflecting these circumstances are rare. In this study, we describe the development of a novel tri-culture model, using non-small cell lung cancer (NSCLC) cell lines (A549 and Colo699) in combination with a fibroblast cell line (SV 80) and two different endothelial cell lines in a hanging drop technology. Endothelial cells aggregated either in small colonies in Colo699 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 29 publications
2
46
0
Order By: Relevance
“…To then further develop even more accurate representations of the natural cellular environment, co-cultures or organ-on-a-chip systems could be incorporated alongside live cell imaging 41,42 . Advancements in spheroid design have already been described in the literature, including angiogenesis models where endothelial networks are introduced into tumor spheroids to mimic the role that endothelial cells play in the tumor microenvironment 43 . Vascularization of the microtumors in an in vitro system has been demonstrated and could represent a major advance in the setup for in vitro experimentation 44 .…”
Section: Discussionmentioning
confidence: 99%
“…To then further develop even more accurate representations of the natural cellular environment, co-cultures or organ-on-a-chip systems could be incorporated alongside live cell imaging 41,42 . Advancements in spheroid design have already been described in the literature, including angiogenesis models where endothelial networks are introduced into tumor spheroids to mimic the role that endothelial cells play in the tumor microenvironment 43 . Vascularization of the microtumors in an in vitro system has been demonstrated and could represent a major advance in the setup for in vitro experimentation 44 .…”
Section: Discussionmentioning
confidence: 99%
“…By these co-cultures a denser spheroid structure and cell-cell interactions can be achieved. These play an important role in EMT and hypoxia [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Spheroids can be used to study the physiological spatial growth of vessel structures, the cell-cell interactions, and as a platform for drug development and discovery (30). Hybrid spheroids, generated by co-culturing two or three types of cell, are useful models to study the interaction between endothelial and tumour/stroma cells in different in vitro models of cancer (56,57) or between endothelial and mural cells in angiogenesis/vasculogenesis. Analysis of endothelial cell/MSC spheroids showed that MSC participated in the formation and stabilisation of luminal tubular structures, similarly to pericyte-like cells (58,59).…”
Section: Scaffold-free Modelsmentioning
confidence: 99%